2021
DOI: 10.1021/acs.jafc.1c04705
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin Diffusivity and In Vitro Gastric Digestion of Soymilk as Affected by Binding of Tea Polyphenols to Soy Proteins

Abstract: This study aimed to investigate the effect of tea polyphenol extract (TPE) on the in vitro gastric digestion of soymilk. Fluorescence recovery after photobleaching was applied to measure pepsin diffusivity in soymilk. The characteristics of soymilk digesta were evaluated by gel electrophoresis, degree of hydrolysis (DH), molecular weight distribution, free amino acid analysis, particle size, antioxidant capacity, and trypsin/chymotrypsin inhibitor activity (TIA/CIA). The binding between soy proteins and tea po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…All samples exhibited the highest digestibility in stage S2, indicating that Pv was unfolded to expose more sites capable of binding to pepsin through the binding of Pv to GA; however, further studies are needed to support this hypothesis. The digestibility of the covalent complex decreased with the increase in polyphenol concentration in S1 and S2, probably because polyphenols were able to inhibit protease activity . However, this protease-specific effect might depend on pH or polyphenol binding affinity, , so protein digestibility appeared to differ under noncovalent conditions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…All samples exhibited the highest digestibility in stage S2, indicating that Pv was unfolded to expose more sites capable of binding to pepsin through the binding of Pv to GA; however, further studies are needed to support this hypothesis. The digestibility of the covalent complex decreased with the increase in polyphenol concentration in S1 and S2, probably because polyphenols were able to inhibit protease activity . However, this protease-specific effect might depend on pH or polyphenol binding affinity, , so protein digestibility appeared to differ under noncovalent conditions.…”
Section: Resultsmentioning
confidence: 98%
“…The digestibility of the covalent complex decreased with the increase in polyphenol concentration in S1 and S2, probably because polyphenols were able to inhibit protease activity. 39 However, this proteasespecific effect might depend on pH or polyphenol binding affinity, 40,41 so protein digestibility appeared to differ under noncovalent conditions. The digestibility of the noncovalent complex first decreased and then increased with the increase in concentrations of polyphenol in stages S1 and S2 because the conformational change of Pv induced by noncovalent binding made it easier to be digested by trypsin.…”
Section: Analysis Of Particle Aggregation and ζ Potentialmentioning
confidence: 99%
“…The amount of cumulative FX released at different digestion times was then analyzed by HPLC. Moreover, the protein profile of the collected digested samples was obtained using sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) experiments using a 15% separating gel and 5% stacking gel . The supernatant of digestive juice was mixed with a 5× loading buffer (reduced) before denaturation at 100 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some studies have shown that tea polyphenols can interact with milk proteins and cause conformational changes, which restricts the ability of pepsin to digest the proteins. 18,36 Other studies have shown that tea polyphenols can directly interact with pepsin and reduce its activity. 11,37 The effects of tea polyphenol addition on proteolysis were more pronounced for the high-fat, than for the low-and medium-fat oat milks.…”
Section: Degree Of Protein Hydrolysismentioning
confidence: 99%